Hereditary gingival fibromatosis – a case report and management using a novel surgical technique - K. Butchi Babu1; Kalwa Pavankumar; B. R. Anuradha; Nupur Arora (Revista Sul-Brasileira de Odontologia, 2012)
Introduction: Hereditary gingival fibromatosis (HGF) is a rare condition presenting varied degrees of gingival enlargement. HGF can present as an isolated entity or as part of a syndrome. Current literatures report a defect in the Son of sevenless-1 gene (SOS1) on chromosome 2p21-p22 (HGF1) as a possible cause of this condition. Case report: A case of a 16-year-old female is reported who presented generalized extensive gingival overgrowth, involving the maxillary and mandibular arches covering almost two thirds to three quarters of all teeth. Diagnosis of HGF was substantiated by the patient’s clinical features, family history and histopathological examination. Treatment was excision of the gingival tissue by a modified gingivectomy technique with both manual instrumentation and electrosurgery. The postoperative course was uneventful and the patient’s aesthetic concerns were addressed. Post-surgical follow-up after 18 months demonstrated no recurrence. Conclusion: Hereditary gingival fibromatosis stands apart from other gingival enlargements in the varied treatment options available and the nature of recurrence post treatment. There is no consensus among authors related to the mode of treatment. Here, in this present case report we highlight a novel surgical technique to deal with the extensive nature of enlargement seen in HGF cases.